1995
DOI: 10.1016/0092-8674(95)90536-7
|View full text |Cite
|
Sign up to set email alerts
|

Sonic hedgehog induces the differentiation of ventral forebrain neurons: A common signal for ventral patterning within the neural tube

Abstract: The vertebrate hedgehog-related gene Sonic hedgehog (Shh) is expressed in ventral domains along the entire rostrocaudal length of the neural tube, including the forebrain. We show here that SHH induces the differentiation of ventral neuronal cell types in explants derived from prospective forebrain regions of the neural plate. Neurons induced in explants derived from both diencephalic and telencephalic levels of the neural plate express the LIM homeodomain protein Isl-1, and these neurons possess distinct iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
309
1
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(322 citation statements)
references
References 47 publications
10
309
1
2
Order By: Relevance
“…A second pathway involving Lmx1b and Ptx3 seems to be important for expression of other aspects of the dopaminergic neuronal phenotype [36]. Shh and FGF8 induce the dopaminergic phenotype when present in appropriate concentrations in specific brain regions [33,37,38]. The receptor for Shh is Smo, which is inhibited by a second protein patched (ptch) when Shh is absent [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…A second pathway involving Lmx1b and Ptx3 seems to be important for expression of other aspects of the dopaminergic neuronal phenotype [36]. Shh and FGF8 induce the dopaminergic phenotype when present in appropriate concentrations in specific brain regions [33,37,38]. The receptor for Shh is Smo, which is inhibited by a second protein patched (ptch) when Shh is absent [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding other potential mediators of the transcription factors' influences on angiogenesis, it is well known that sonic hedgehog (Shh) induces Nkx2.1 expression 35,36 and that Shh has pivotal roles in both neurogenesis and angiogenesis 37 . In Nkx2.1 −/− mutants, at E10.5 and E11.5, Shh expression is virtually undetectable in the basal telencephalon 12 .…”
Section: Compartmental Influences On Telencephalic Angiogenesismentioning
confidence: 99%
“…Because vertebrate and Drosophila eye development appear to require many of the same transcription factors, it is plausible that they would require some of the same cell-signaling molecules (for review, see Reh and Cagan, 1994). Second, in vertebrates, members of the Hedgehog family have been shown to act as inducing molecules for particular cell fates in spinal cord and mesencephalon (Roelink et al, 1994;Ericson et al, 1995;Hynes et al, 1995), and it is likely that these molecules play important roles in the overall patterning of the developing nervous system (Ekker et al, 1995b). Third, in vertebrates, Sonic hedgehog (Shh) expression in the zone of polarizing activity can be induced by retinoic acid (RA) (for review, see Johnson and Tabin, 1995), and recently we have reported that RA can act as a rod photoreceptor inducer in embryonic rat retinal cell cultures (Kelley et al, 1994.…”
Section: Abstract: Sonic Hedgehog; Indian Hedgehog; Desert Hedgehog;mentioning
confidence: 99%